Developing Cultural Tourism Potentials of Ngabab Village, Pujon District, Malang Regency - Muhammad Edy Thoyib; Istiadah Istiadah; Syafiyah Syafiyah; Miftahul Huda (Warta Pengabdian, 2022)
This article provides the academic report on the administration of community service program to develop cultural tourism in Ngabab village, Pujon, Malang. The program aims at identifying Ngabab’s potentials of cultural tourism, empowering the village’s stakeholders, particularly the youths, and forming tourism movement communities. Participatory Action Research (PAR) method is applied by following five sequential steps: problem identification, planning, action, observation, and reflection. The result of the study shows that developing the potentials of cultural tourism in Ngabab village is viable through focus group discussion, capacity building on short film production, website design, and guiding/tourism service, and establishment of tourism awareness group and film community. The program sustainability may be guaranteed by mutual cooperation with the Ministry of tourism affairs, private companies, and any related stakeholders in the regency.